Band Gap of Atomically Precise Graphene Nanoribbons as a Function of Ribbon Length and Termination. Issue 18 (21st August 2019) - Talirz, Leopold; Söde, Hajo; Kawai, Shigeki; Ruffieux, Pascal; Meyer, Ernst; Feng, Xinliang; Müllen, Klaus; Fasel, Roman; Pignedoli, Carlo A.; Passerone, Daniele
Abstract: We study the band gap of finite N A = 7 armchair graphene nanoribbons (7‐AGNRs) on Au(111) through scanning tunneling microscopy/spectroscopy combined with density functional theory calculations. The band gap of 7‐AGNRs with lengths of 8 nm and more is converged to within 50 meV of its bulk value of ≈ 2 . 3 eV, while the band gap opens by several hundred meV in very short 7‐AGNRs. We demonstrate that even an atomic defect, such as the addition of one hydrogen atom at the termini, has a significant effect – in this case, lowering the band gap. The effect can be captured in terms of a simple analytical model by introducing an effective "electronic length". Abstract : The band gap of atomically precise graphene nanoribbons with lengths in the sub‐10 nm regime varies significantly both with their length and termination.